Accounting of current liabilities and settlements in a market economy - Vafokhojaeva Dilafruz Marufovna (Global Scientific Publishing, 2022)
within the enterprises operating in our Republic, small and mediumsized economic entities play an important role. An important task is also to improve the accounting of obligations arising during the period of mutual settlements between them in a period when great attention is paid to the development of an economic entity. Until the independence of the Republic of Uzbekistan, all property was owned by the state, and all calculations between them were carried out according to the plan established by the state. Enterprises were engaged only in the implementation of the established plan. In such conditions, the accounting of mutual settlements between them and, moreover, the mutual settlements themselves did not have any significance.
Keywords: market economy; income; expenses; economic entities